Entrepreneurship theory, process, practice - Kuratko, Donald F.; Hodgetts, Richard M. (Thomson / South-Western, 2007)
This seventh edition combines a step-by-step approach with a theoretical foundation to form a basic framework for understanding the process of entrepreneurship. It provides learners with the opportunity to apply ideas and develop useful analytical skills.